Education Technologies and Institutional Boundaries: Education–Business Interaction in the Context of Industry 5.0 - Papachashvili, Nino; Mikaberidze, Tamta; Tavartkiladze, Marine (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
This study examines how education technologies influence institutional boundaries in the interaction between formal education systems and business organizations under Industry 5.0. While existing research has largely focused on the pedagogical role of digital learning, less attention has been given to how education technologies reshape the interaction between education and business as an integrated institutional process. Moving beyond their pedagogical function, education technologies are conceptualized here as institutional mediators that redistribute responsibilities for knowledge and skill formation across sectors. Using an institutional–analytical approach complemented by an illustrative case of Georgia, the paper shows that adaptive learning ecosystems expand more actively in contexts where foundational competencies are already present. This suggests that education technologies operate as capability-enhancing mechanisms rather than substitutes for formal education. The findings point to a reconfiguration of education–business interaction characterized by differentiated and context-dependent role distribution. At the same time, they highlight a potential tension between the inclusive aspirations of Industry 5.0 and the selective dynamics of market-driven training systems.